2019
DOI: 10.1002/aisy.201900051
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint‐Enhanced Capacitive‐Piezoelectric Flexible Sensing Skin to Discriminate Static and Dynamic Tactile Stimuli

Abstract: Inspired by the structure and functions of the human skin, a highly sensitive capacitive‐piezoelectric flexible sensing skin with fingerprint‐like patterns to detect and discriminate between spatiotemporal tactile stimuli including static and dynamic pressures and textures is presented. The capacitive‐piezoelectric tandem sensing structure is embedded in the phalange of a 3D‐printed robotic hand, and a tempotron classifier system is used for tactile exploration. The dynamic tactile sensor, interfaced with an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(103 citation statements)
references
References 48 publications
0
93
0
Order By: Relevance
“…For example, the viscoelastic medium between contact point on the skin surface and the receptor deep inside the soft skin could alter the response of receptors. In addition, the neuroscience studies have confirmed the presence of plasticity or synaptic modulation in biological neural systems referring to the ability of synapse to weaken or strengthen the synaptic weights with respect to the tactile activity over the time [2][3][4][5][6][7]. These observations have profound implications for the development of future large area tactile skin.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…For example, the viscoelastic medium between contact point on the skin surface and the receptor deep inside the soft skin could alter the response of receptors. In addition, the neuroscience studies have confirmed the presence of plasticity or synaptic modulation in biological neural systems referring to the ability of synapse to weaken or strengthen the synaptic weights with respect to the tactile activity over the time [2][3][4][5][6][7]. These observations have profound implications for the development of future large area tactile skin.…”
Section: Introductionmentioning
confidence: 83%
“…Skin is the largest organ in the human body (overall surface area of 1.5-2.0 m 2 ) [1], which houses a network of distributed and energy-aware receptors at various depths in the soft tissues [2][3][4]. These receptors (mechanoreceptors (pressure/force), nociceptors (pain) and thermoreceptors (temperature)) enable us to feel and perceive various contact parameters [2][3][4] and give us the most vital of the five essential senses (sight, hearing, touch, smell, taste). Based on the stimuli the mechanoreceptors respond to, their classification as SAs (slow adapting) and FAs (fast adapting) is well known [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations